Religious Digital Creatives in Türkiye: A Research on the Axis of Algorithmic Authority - Yunus Ergen (Türkiye İletişim Araştırmaları Dergisi)
In recent years, there has been a significant increase in the amount of religious digital content in Türkiye.This trend is fueled by the contributions of various content creators and the flexibility of social mediaplatforms. The quantitative density of digital content enables content creators to be perceived as authoritiesin their respective fields. The most recent approach for understanding authority derived from the contentgenerated in digital media is algorithmic authority. This approach is also employed to analyze the structureof religious digital content creators and the content they create. This study aims to reveal who createsreligious digital content in Türkiye, to classify the structure of the content created, and to evaluate the level ofauthority of these creators in the focus of algorithmic authority. To achieve this, 176 YouTube channels thatcreate religious content were indexed and analyzed using content analysis. These channels were classifiedinto five categories: algorithmic authority, structure of channel, structure of content, type of content, andmonetization. The study found that algorithmic authority varied based on the number of subscribers,videos, and total views, but the vast majority of channels had the highest algorithmic authority in termsof total views. Most of the content was created by religious communities, and the theme of fundamentalreligious sciences was prevalent. The majority of channels generate income through content monetization.The research indicates that religious digital creatives in Türkiye have high algorithmic authority, continuetheir activities with different organizations, and have diverse content.